PENGALAMAN KOMUNIKASI PEMERINTAH KOTA PADANG DALAM PENANGGULANGAN MASALAH PROSTITUSI TERSELUBUNG DI KOTA PADANG - Atika Atika; Elva Ronaning Roem; Sarmiati Mia; Najmuddin Rasul (Jurnal Ranah Komunikasi, 2022)
The issue of prostitution is a hot topic of discussion, because its existence raises pros and cons in society. Covert prostitution in Padang City is still a problem for the Padang City Government. The Padang City Government is carrying out countermeasures as a form of enforcing the Regional Regulations. Government communication is defined as a form of conveying government ideas, programs and ideas to the public with the aim of mutual welfare. Researchers looked at how the Padang City Government's communication experience in tackling covert prostitution in Padang City This study used a qualitative method and a phenomenological approach proposed by Edmund Husserl. The Padang City Government, through several OPDs (Satpol PP, Social Service, DP3AP2KB), has made efforts to tackle covert prostitution. His efforts include making routine arrests and raids on lodging locations and massage parlors. Perpetrators involved in prostitution will be immediately sent to the Andam Dewi rehabilitation center. Apart from that, they also carried out socialization in the form of direct communication at the sub-district level in Padang City. Communication experience The Padang City Government has attempted to tackle covert prostitution. coping efforts that are outreach, routine raids, sending to rehabilitation institutions, and informal communication through psychologists.